In Vitro Effect of Sorghum (Sorghum bicolor) Seed Extracts as a Biological Acaricidal Against Some Hard Tick (Ixodidae) in Sulaimani Governorate - Kurdistan Region/Iraq - Mustafa, Bahzad H.S.; Mohammad, Kadhm A.; Mahammed, Aram O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
This study was conducted in Sulaimani governorate in order to identify the biological control of some Ixodidae genera among different flocks of cattle, sheep and goats. Four genera of Ixodidae; Boophilus spp., Hyalomma spp., Rhipicephalus spp. and Haemaphysalis spp., were identified in these infested animals. According to chi–square test, the highest distribution of Boophulis spp., was recorded in cattle (56.51%), and the highest distribution of Hyalomma spp., (49.82%) and Rhipicephalus spp., (28.16%) which were in sheep. The highest number of Haemophasylas spp., was obtained from goats (6.67%), whereas the lowest number of this genus (2.88% and 2.89%) was collected from cattle and sheep respectively. The toxicity of Sorghum bicolor seed extract was tested against the more distributed Ixodidae genera (Boophilus spp. and Hyalomma spp.) by immersion method on mature ticks, four concentrations (23.2, 17.4, 11.6 and 5.8 mg/dl), in addition to the control treatment (0 mg/dl) of the seed were used to evaluate the engorged females in vitro. The results showed that 100% of absolute cumulative mortality of Boophilus spp., was gain after 72 hr by 23.2 mg/dl extract concentration, followed by 17.4 mg/dl which gave 90% mortality, whereas 100% absolute cumulative mortality for Hyalomma spp., was obtained by 23.2 mg/dl extract concentration after 48 hr, followed by 17.4, 11.6 and 5.8 mg/dl concentration that gave 90%, 80% and 40% mortality after 72 hr.